1997
DOI: 10.1002/(sici)1097-0347(199701)19:1<41::aid-hed8>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Palliative treatment with low-dose continuous infusion 5-fluorouracil in recurrent and/or metastatic undifferentiated nasopharyngeal carcinoma type

Abstract: Significant advances in identification of etiologies of inherited thrombosis have been recently reported. A point mutation in coagulation factor V (factor V Leiden) results in resistance to activated protein C and probably represents the most common genetic risk factor for venous thrombosis. A metabolic disorder, homocysteinemia, is now known to be an important risk factor for both arterial and venous thrombosis. Many patients with recurrent thrombosis will have more than one genetic risk factor identified. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…They found that the treatment did not require interruption for up to 60 days at dose rates of 300 mg/m 2 /d or less. [21] Fandi et al [22] reported that treatment with low-dose continuous infusion 5-fluorouracil in recurrent and/or metastatic undifferentiated NPC was safe and effective. Administration of 5-Fu (300 mg/m 2 /d) for 6 weeks resulted in an objective response rate of 25% and mild toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the treatment did not require interruption for up to 60 days at dose rates of 300 mg/m 2 /d or less. [21] Fandi et al [22] reported that treatment with low-dose continuous infusion 5-fluorouracil in recurrent and/or metastatic undifferentiated NPC was safe and effective. Administration of 5-Fu (300 mg/m 2 /d) for 6 weeks resulted in an objective response rate of 25% and mild toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of 5-Fu (300 mg/m 2 /d) for 6 weeks resulted in an objective response rate of 25% and mild toxicity. [22] Therefore, a continuous intravenous infusion of 5-Fu at the dose of 200 mg/m 2 /d for 30 days in the treatment of refractory NPC was considered safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the selected anticancer drug may not show the same efficacy with respect to metastatic and recurrent tumors. 17,18 Furthermore, the possibility of metastatic and recurrent tumors acquiring resistance to the anticancer drug as a result of primary therapy cannot be eliminated, and more detailed investigation will be necessary in the future with regard to this point.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that low-dose chemotherapy may reduce toxic effects while maintaining or even improving efficacy, compared with the conventional dose of chemotherapy used for treatment of metastatic carcinoma. 16 , 17 , 18 , 19 For recurrent or metastatic NPC, a phase 2 trial of fluorouracil infusion at a dose of 300 mg/m 2 for 6 consecutive weeks found a median survival of 10 months and mild toxic effects. 18 Fluorouracil is a cell cycle–dependent drug whose cytotoxicity is proportional to the cell proliferation rate and to the drug exposure time.…”
Section: Introductionmentioning
confidence: 99%